step by step solution

Recall the **Recursive formula for an arithmetic sequence**:

The recursive formula for the nth term of an arithmetic sequence for which the first term is a1 and the common difference is **d** is given with:

a_n=a_{n-1}+d

and, it is given that:

f(n)=f(n-1)+7\implies d=7

Let **f(1)** represent the first term of the arithmetic sequence series:

It means,

f(1)=a_{1}=-18

Similarly,

f(37)=a_{37}

**nth Term of an Arithmetic Sequence**:

The **nth** term of an arithmetic sequence with the first term** a1** and the common difference **d** is given by:

a_n=a_1+(n-1)d

on substituting the values in the above equation:

a_{37}=-18+(37-1)7\implies a_{37}=234

Hence, the required value of ** f(37)=234**

You may be like this post: